The Realization of Factors Detrimental to State Finances in Corporate Activ-ities - Ainuddin , Ainuddin (Institute for Law and Economics Studies, 2025)
The realization of state financial loss in corruption offenses involves demonstrating that a corrupt act has caused a tangible and specific detriment to state finances or the national economy. This study examines the clarity of legal material regarding state financial loss in corporate actions, focusing on the corruption case verdict No. 70/Pid.Sus-TPK/2023/PN.Plg. Using a normative legal methodology—incorporating legislative, conceptual, and case law studies, the study examines the legal frameworks surrounding corruption and state budget cuts, revealing differing interpretations of financial loss in corporate corruption cases. It emphasizes the need for clearer instructions on proving state financial loss and emphasizes the importance of a strong legal base in corruption cases. Findings reveal that the Public Prosecutor failed to convincingly establish the legal basis for proving state financial loss. The indictment claimed that PT. BA’s acquisition of PT. SBS through its subsidiary PT. BMI resulted in a state financial loss of IDR 162,466,152,401. However, inconsistencies emerged in defining